Titanium-doped high-nickel ternary positive electrode material and preparation method thereof
By doping reducing titanium into high-nickel ternary cathode material, and improving the material structure by redox reaction and Ti-O bonds, the stability and performance problems of high-nickel ternary cathode material are solved, and excellent cyclic stability and rate performance are achieved, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202510019177.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-07
AI Technical Summary
The high-nickel ternary cathode material has problems such as phase change in the surface particles, poor magnification and circulation performance, unstable surface structure, and poor thermal stability. The existing modification methods have defects such as moisture influence, difficulty in controlling gas flow rate and concentration, which affect industrial applications.
By mixing and sintering the reducing titanium-containing compound with a high-nickel ternary positive electrode material, titanium-doped elements are formed, and Ni2+ is enriched on the surface of the material by redox reaction, forming a stable protective layer, and improving the lattice structure strength of the material through Ti-O bonds.
It improves the cycle stability and rate performance of the material, reduces the corrosion of the electrolyte on the material, enhances the structural stability of the material, and is suitable for industrial production.
Smart Images

Figure CN119812299A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery positive electrode materials, and in particular to a titanium-doped high-nickel ternary positive electrode material and a preparation method thereof. Background Art
[0002] High nickel ternary cathode material Li(Ni x Co y Mn 1-x-y )O2 (LNCM) has higher specific capacity and energy density, has greater advantages in the application of new lithium-ion batteries, and is considered to be one of the most promising positive electrode materials for power lithium-ion batteries. However, high-nickel positive electrode materials have problems such as easy phase change of surface particles, poor rate and cycle performance, unstable surface structure, and poor thermal stability. Structural modification can improve the stability of high-nickel ternary materials to a certain extent and enhance the electrochemical performance of the materials.
[0003] The patent document with publication number CN112736229 A discloses a reduction-modified lithium positive electrode material and a preparation method thereof. The method uses hypophosphorous acid and / or hypophosphite as a reducing agent, and after pre-treatment, the reducing agent is coated on the surface of the lithium positive electrode material as evenly as possible, and an interface phase structure of a spinel phase and / or a rock salt phase is constructed on the surface, thereby protecting the main body of the material from electrolyte erosion and improving the material cycle stability. The method uses calcium hypophosphite, sodium hypophosphite, hypophosphorous acid, and magnesium hypophosphite as reducing agents to modify the positive electrode material, and uses the reducing gas PH3 generated by high-temperature decomposition to reduce and modify the surface of the material. The method makes the coating layer tighter through reaction to achieve uniform and firm coating, and does not explain the specific reaction of the modification, and how to achieve tight coating. And the method involves the use of water as a solvent in the experimental process. Water will have a serious impact on the performance of the high-nickel positive electrode material. Water will generate inert lithium salts on the surface of the material, destroying the material structure and reducing the material performance. The high-nickel material must control the humidity during the coating process, which is generally carried out in an anhydrous environment. In addition, the use of gas to modify materials is affected by many factors such as gas flow rate, concentration, temperature and time. The amount of reducing agent is difficult to control accurately, and there is no obvious guiding significance for the use of reducing agents to modify positive electrode materials, which is not conducive to industrial applications. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology, and to provide a titanium-doped high-nickel ternary positive electrode material with good electrochemical properties such as good structural stability, cycle performance, and rate performance, and a preparation method thereof.
[0005] In order to solve the above technical problems, the technical solution proposed by the present invention is: A titanium-doped high-nickel ternary positive electrode material, characterized in that the titanium-doped high-nickel ternary positive electrode material comprises a high-nickel ternary positive electrode material and a titanium doping element; the titanium doping element is derived from a reducing titanium-containing compound, which is mixed and sintered with the high-nickel ternary positive electrode material to form a doping element; the content of the titanium doping element accounts for 0.5-5wt% of the titanium-doped high-nickel ternary positive electrode material, and the reducing titanium-containing compound includes one or more of titanium monoxide, titanium dichloride, and titanium dibromide.
[0006] The present invention uses reducing titanium to modify the high-nickel ternary material, and through redox reaction, the more stable Ni 2+ It is enriched on the surface of the material as a protective layer, which reduces the corrosion of the electrolyte on the material and improves the surface stability of the material. At the same time, titanium can enter the material lattice more easily than general doping methods. The strong Ti-O bond improves the strength of the material lattice structure, achieving excellent cycle stability and rate performance.
[0007] More preferably, the chemical formula of the high nickel ternary positive electrode material is LiNi x Co y Mn (1-x-y) O2, wherein 0.75<x<0.95, 0.025<y<0.1; the high-nickel ternary positive electrode material is a spherical secondary particle agglomerate with a particle size of 2-4μm.
[0008] The packing density of powder materials is closely related to their morphology, particle size and distribution. When irregularly shaped powder particles are mixed, there are serious agglomeration and ion bridging phenomena. When the particles are stacked and filled, there are large gaps between the particles, and the powder packing density is low. When regular spherical particles are stacked and filled, the contact surface between the particles is small, there is no agglomeration and particle bridging phenomenon, there are fewer gaps between the particles, and the powder packing density is high. The microstructure of the morphology and particle size of the positive electrode material depends on the precursor. Spheroidization of the precursor material particles is an effective way to increase the material packing density and volumetric capacity, and the spherical product has excellent fluidity, dispersibility and processability. Therefore, spheroidization can increase the compaction density and volumetric capacity of the positive electrode material and improve its processing performance and the quality of the electrode. A titanium-doped high-nickel ternary positive electrode material is obtained by mixing a reducing titanium compound with a high-nickel ternary positive electrode material and then solid-phase sintering to obtain a spherical titanium-doped high-nickel ternary positive electrode material, which ensures the morphology and particle size distribution of the secondary spherical particles of the original ternary material; the titanium-doped high-nickel ternary positive electrode material inherits the morphology of the spherical secondary particle agglomerates, with regular morphology and uniform distribution.
[0009] Based on the same technical idea, the present invention also provides a method for preparing a titanium-doped high-nickel ternary positive electrode material, comprising the following steps: (1) Preparation of nickel-cobalt-manganese hydroxide precursor by coprecipitation reaction; (2) uniformly mixing the nickel-cobalt-manganese hydroxide precursor obtained in step (1) with a lithium source, performing two-stage sintering in an oxidizing atmosphere, and cooling to room temperature to obtain a high-nickel ternary positive electrode material; (3) mixing the high-nickel ternary positive electrode material obtained in step (2) with the reducing titanium source; (4) Sintering the mixed powder obtained in step (3) at high temperature in an inert atmosphere, keeping it for a period of time and then cooling it to obtain a titanium-doped high-nickel ternary positive electrode material.
[0010] High nickel materials have problems such as unstable surface structure, transition metal dissolution, and electrolyte corrosion, especially the highly reactive Ni 3+ The reaction with the electrolyte will cause the surface structure to deteriorate, lattice oxygen to precipitate and electrochemically inert substances to form. 3+ Reduction to stable Ni 2+ , and make Ti 4+ Better incorporation into the material lattice can stabilize the material structure and improve the rate and cycle performance. At the same time, the stronger Ti-O bond can enhance the material structure strength and inhibit the precipitation of lattice oxygen caused by charge transfer, thus improving the material's cycle stability and rate performance.
[0011] Further preferably, the preparation of the nickel-cobalt-manganese hydroxide precursor by coprecipitation reaction in the above step (1) refers to pumping the nickel-cobalt-manganese mixed solution into a continuous stirring reactor filled with an ammonia solution, heating and introducing a protective atmosphere, and simultaneously pumping in a complexing agent and a precipitant solution, stirring for coprecipitation reaction, aging, filtering, washing and drying to obtain the nickel-cobalt-manganese hydroxide precursor.
[0012] Further preferably, the nickel source, manganese source and cobalt source in the above-mentioned nickel-cobalt-manganese mixed solution are soluble nickel salt, soluble manganese salt and soluble cobalt salt, respectively; the total molar concentration of nickel, cobalt and manganese ions in the nickel-cobalt-manganese mixed solution is 0.1-3.0 mol / L, and the molar ratio of the nickel, cobalt and manganese ions is (7.5-9.5): (0.25-2.5): (0.25-2.5); the feeding rate of the nickel-cobalt-manganese mixed solution is 80-120 mL / h.
[0013] If the concentration of metal ions in the nickel-cobalt-manganese mixed solution is too low, it will be detrimental to the subsequent precipitation process, and the precipitation time will be long, which is not conducive to improving production efficiency; if the concentration of metal ions is too high, it will be detrimental to the complete dissolution of metal salts. If the feeding speed is too fast, it will lead to a large pH change range, making it difficult for the precipitant to effectively precipitate the metal ions, which is not conducive to controlling the formation and growth of crystal nuclei in the reaction process. If the feeding speed is too slow, the particles are easy to agglomerate, which is also not conducive to improving production efficiency.
[0014] Further preferably, the above-mentioned soluble nickel salt is one or more of nickel sulfate, nickel nitrate, nickel acetate or nickel chloride, and hydrates thereof; the soluble cobalt salt is one or more of cobalt sulfate, cobalt nitrate, cobalt acetate or cobalt chloride, and hydrates thereof; the soluble manganese salt is one or more of manganese sulfate, manganese nitrate, manganese acetate or manganese chloride, and hydrates thereof. The total molar concentration of nickel, cobalt and manganese ions in the nickel-cobalt-manganese mixed solution is more preferably 1.5-2.5 mol / L. The feeding rate of the nickel-cobalt-manganese mixed solution is more preferably 90-110 mL / h.
[0015] Further preferably, the complexing agent is an ammonia solution, the mass concentration of ammonia in the ammonia solution is 25-28%; the ammonia concentration of the reaction system is adjusted to 0.1-5.0 mol / L by using the ammonia solution; the precipitant is one or more of sodium hydroxide, potassium hydroxide or lithium hydroxide, and the molar concentration of the precipitant solution is 1.0-7.0 mol / L; the pH value of the reaction system is adjusted to 10-12 by using the precipitant solution; the volume ratio of the ammonia solution, the precipitant solution and the nickel-cobalt-manganese mixed solution is (0.1-10):(1-2):(1-2).
[0016] If the molar concentration of the ammonia solution is too low, it is difficult for the metal ions to be completely complexed. If the molar concentration of the ammonia solution is too high, it is not conducive to the formation of hydroxide precipitation by the metal ions. If the molar concentration of the hydroxide precipitant solution is too high or too low, the reaction process cannot be accurately controlled. At the above pH value, it is more conducive to controlling the particle growth rate to be not too fast or too slow. Under the volumetric feeding ratio of the above ammonia solution, the precipitant solution and the nickel-cobalt-manganese mixed solution, the formation of crystal grains and crystal growth in the crystallization process are conducive.
[0017] Further preferably, during the above coprecipitation reaction, the stirring speed is controlled to be 800-1200 r / min, the temperature is 30-60°C, and the time is 30-50h; the aging temperature is 30-60°C; the washing is to cross-wash the filtrate with deionized water and ethanol respectively for ≥6 times; the drying temperature is 80-100°C, and the time is 12-24h.
[0018] If the stirring speed is too slow, the primary particles are prone to agglomeration. If the stirring speed is too fast, the growing crystals are prone to breakage. Within the above temperature range, it is more conducive to the growth of crystals. The reaction time is determined by the raw material content and the feeding speed. The aging process can replace anions such as sulfate inside the material and is conducive to the uniformity of the particle surface. If the aging time is too short, it is difficult to ensure the ion exchange of anions, which will also affect the subsequent washing process. If the aging time is too long, it will be detrimental to production application and the uniformity of the material surface. The above aging temperature is consistent with the coprecipitation reaction temperature, which is conducive to the uniform dispersion of the material without agglomeration, and ensures that the primary particles grow uniformly into secondary particles. If the drying temperature is too low or the time is too short, the material is difficult to dry. If the temperature is too high or the time is too long, there will be other side reactions on the material surface, affecting the material performance, and the cycle is too long, which is not conducive to industrial production.
[0019] More preferably, the stirring temperature during the coprecipitation reaction is controlled to be 40-50° C. The aging temperature is more preferably 40-50° C.
[0020] Further preferably, in the above step (2), the lithium source is lithium hydroxide and / or lithium carbonate, and the molar ratio of the total molar amount of nickel, cobalt and manganese elements in the nickel-cobalt-manganese hydroxide precursor to the lithium element in the lithium source is 1:(1.02-1.2).
[0021] Further preferably, in the above step (2), the two-stage sintering is firstly heated to 350-550°C at a heating rate of 1-10°C / min, sintered for 2-8h, and then heated to 550-1000°C at a heating rate of 1-10°C / min, and sintered for 8-20h.
[0022] Further preferably, the two-stage sintering is firstly heating to 400-500°C at a heating rate of 3-7°C / min, sintering for 3-6h, and then heating to 600-900°C at a heating rate of 3-7°C / min, and sintering for 10-16h.
[0023] In the two-stage temperature-raising sintering process, the temperature of the second stage sintering is higher than that of the first stage sintering. In the first stage sintering process, the decomposition reaction of the precursor and the lithium source mainly occurs. In the second stage sintering process, the combination reaction of the precursor and the oxide decomposed from the lithium source in an oxygen atmosphere mainly occurs. If the sintering temperature is too high or the time is too long, the material is prone to agglomeration or even agglomeration, and it is difficult to release the capacity during the charge and discharge process. If the calcination temperature is too low or the time is too short, it is difficult to form the desired morphology, affecting the electrochemical performance. If the heating rate is too fast, it is difficult to ensure that the material reacts fully, especially affecting the diffusion of lithium ions into the material structure. If the heating rate is too slow, it is not conducive to industrial production.
[0024] Further preferably, in the above step (3), the mass ratio of the high-nickel ternary positive electrode material to the reducing titanium source is 1:(0.005-0.05); the titanium source is one or more of titanium monoxide, titanium dichloride, titanium dibromide and other reducing titanium-containing compounds.
[0025] Further preferably, in the above step (3), the mass ratio of the high nickel ternary positive electrode material to titanium monoxide is 1: (0.005-0.05). If the amount of titanium source is too much, the unreacted titanium-containing substances on the surface of the material will accumulate too much, which will affect the reaction process kinetics of the material and thus affect the performance of the material. If the amount of titanium source is too little, it is difficult to achieve the modification effect and it will cause a waste of raw materials.
[0026] Further preferably, in the above step (4), the high temperature sintering is to heat the temperature to 300-500°C at a heating rate of 1-10°C / min and sinter for 3-5h; and the inert atmosphere is an argon atmosphere and / or a nitrogen atmosphere.
[0027] Further preferably, the high temperature sintering is to increase the temperature to 400° C. at a heating rate of 3-7° C. / min and sinter for 3-5 hours.
[0028] The purpose of sintering is to allow the titanium source to be adsorbed on the surface of the high nickel ternary material, while at the same time 2+ with Ni 3+ The reaction causes Ti 4+ Better enter the material lattice to form a stable Ni 2+ If the heating rate is too fast, it is difficult to ensure that the material reacts fully. If the heating rate is too slow, it is not conducive to industrial production. If the sintering temperature is too low, Ti 2+ Difficult to oxidize to form Ti 4+ If the sintering temperature is too high, the ions may enter the material phase too quickly, resulting in uneven modification. If the sintering time is too short, the reaction will be incomplete. If the sintering time is too long, unnecessary side reactions will occur and affect production efficiency.
[0029] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses reducing titanium to modify the high-nickel ternary material, and makes the more stable Ni 2+ It accumulates on the surface of the material and acts as a protective layer to reduce the corrosion of the electrolyte on the material and improve the surface stability of the material. At the same time, it makes it easier for titanium to enter the material lattice than general doping methods. The stronger Ti-O bonds improve the strength of the material lattice structure, resulting in excellent cycle stability and rate performance.
[0030] (2) The titanium-doped high-nickel ternary positive electrode material prepared by the present invention is a spherical secondary particle agglomerate with an average particle size of 3 μm, regular morphology, and uniform distribution; it has excellent cycle stability and rate performance. The charge capacity is above 210 mAh / g, the first charge and discharge coulomb efficiency is above 80%, and the capacity retention rate is above 70% after 150 cycles.
[0031] (3) The preparation method of the present invention modifies the high-nickel ternary positive electrode material by a solid phase sintering method, which has a simple process, low reaction temperature, low raw material cost, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 This is the XRD diagram of the titanium-doped high-nickel ternary positive electrode material of Example 1 of the present invention; Figure 2 This is a SEM image of the titanium-doped high-nickel ternary positive electrode material of Example 1 of the present invention; Figure 3 This is the EDS Mapping diagram of the titanium-doped high-nickel ternary positive electrode material of Example 1 of the present invention; Figure 4 It is a charge-discharge cycle curve and a charge-discharge Coulomb curve diagram of a battery assembled with a titanium-doped high-nickel ternary positive electrode material according to Example 1 of the present invention; Figure 5 This is a discharge curve diagram of different rates of a battery assembled with titanium-doped high-nickel ternary positive electrode material according to Example 1 of the present invention. DETAILED DESCRIPTION
[0034] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0035] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0036] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0037] The present invention utilizes the reducible titanium-doped high-nickel ternary positive electrode material surface to obtain a stable Ni 2+ and Ti 4+ The doped surface improves the material's cycle performance and rate performance. Specifically: Mix evenly and heat-treat at high temperature in an inert atmosphere to make the highly reactive Ni on the material surface 3+ Reduction to stable Ni 2+ , Ti 2+ Oxidized to Ti 4+ , which allows titanium to be better incorporated into the lattice and stabilizes the surface Ni 2+ The layer inhibits the side reactions on the surface of the material during the charge and discharge cycle, preventing the corrosion of the electrolyte and the generated Ni 2+ The charge balance inhibits the oxidation of lattice oxygen and alleviates the surface oxidation caused by Ni 3+ The spontaneous reduction leads to the precipitation of lattice oxygen, which reduces the formation of oxygen vacancies, enhances the stability of the material structure, and improves the cycle performance. The Ti-O bond dissociation energy is very strong, which enters the lattice to improve the structural strength, inhibits the structural collapse in the de-lithiation state, provides more lithium ion transmission channels, reduces the generation of microcracks, and enhances the rate performance of the material to a certain extent. The following is further explained in conjunction with the embodiments.
[0038] Example 1 A titanium-doped high-nickel ternary positive electrode material and a preparation method thereof.
[0039] The positive electrode material is made of titanium-doped high-nickel ternary positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 O2, the titanium oxide content in the titanium-doped high-nickel ternary positive electrode material accounts for 1% of the positive electrode material, LiNi 0.9 Co 0.05 Mn 0.05 O2 is a spherical secondary particle agglomerate with an average particle size of 3 μm, regular morphology and uniform distribution. The method for preparing the titanium-doped high-nickel ternary positive electrode material in this embodiment includes the following steps: (1) 4 L of a mixed solution of transition metal solution nickel sulfate, cobalt sulfate and manganese sulfate, wherein the total molar concentration of Ni, Co and Mn ions is 2.0 mol / L, is pumped into a reactor containing 2 L, 2 mol / L ammonia solution at a feeding rate of 100 mL / h, and at the same time, the ammonia concentration of the reaction system is adjusted to 2 mol / L with 25% ammonia solution, and the pH value of the reaction system is adjusted to 11.4 with 4 L, 5 mol / L sodium hydroxide precipitant solution, and a high-purity nitrogen atmosphere is introduced, and heated and stirred at 1000 r / min and 50° C. for 20 h for coprecipitation reaction, and then stirred and aged at 45° C. for 12 h, filtered, and the filtrate is cross-washed with deionized water and ethanol for 6 times, respectively, and dried at 90° C. for 12 h to obtain a nickel-cobalt-manganese hydroxide precursor; (2) 2.0 g of the nickel-cobalt-manganese hydroxide precursor (Ni 30.6696 mmol, Co 1.6968 mmol, Mn 1.8201 mmol) obtained in step (1) was mixed with 0.9478 g (35.8958 mmol) of lithium hydroxide monohydrate and ball-milled. The mixture was heated to 450 °C at a rate of 5 °C / min in a high-purity oxygen atmosphere and sintered for 4 h. The mixture was then heated to 700 °C at a rate of 5 °C / min and sintered for 12 h. The mixture was sintered in two stages and cooled to room temperature to obtain high-nickel ternary LiNi 0.9 Co 0.05 Mn 0.05 O2 cathode material; (3) 0.01 g of titanium monoxide powder obtained in step (2) was mixed with 1.0 g of high-nickel ternary LiNi 0.9 Co 0.05 Mn 0.05 The O2 cathode material is fully mixed and uniformly in the ball mill; (4) The powder obtained in step (3) is transferred into a tube furnace and heated to 400°C at a rate of 5°C / min under an argon atmosphere, sintered for 4 h, and cooled to room temperature to obtain a titanium-doped high-nickel ternary positive electrode material.
[0040] like Figure 1 As shown, the titanium-doped high-nickel ternary positive electrode material of this embodiment is consistent with the characteristic peaks of PDF card LiNiO2 (PDF#85-1966) (due to the high nickel content of the high-nickel ternary positive electrode material, the characteristic peaks reflected by XRD are almost the same as those of pure lithium nickelate, and the structural characteristics are consistent), and no impurities are generated.
[0041] like Figure 2 As shown, the titanium-doped high-nickel ternary positive electrode material of this embodiment has a good morphology, inheriting the morphology of the high-nickel ternary positive electrode material, and the secondary particles are spherical with an average particle size of 3 μm.
[0042] like Figure 3As shown, the EDS mapping results of the titanium-doped high-nickel ternary positive electrode material of this embodiment show that the titanium element is evenly distributed on the material.
[0043] Battery assembly: Weigh 0.08 g of the titanium-doped high-nickel ternary positive electrode material obtained in this example, add 0.01 g of acetylene black as a conductive agent and 0.01 g of PVDF polyvinylidene fluoride as a binder, and mix and grind with N-methylpyrrolidone as a solvent to form a positive electrode material; apply the obtained positive electrode material on the surface of an aluminum foil to form a pole piece; in a closed glove box filled with argon, use the pole piece as the positive electrode, the metal lithium sheet as the negative electrode, the microporous polypropylene film as the separator, and 1 mol / L LiPF6 / EC:DMC:EMC (volume ratio 1:1:1) as the electrolyte to assemble a CR2025 button battery, and perform a charge and discharge performance test.
[0044] like Figure 4 As shown, the battery assembled by the method of obtaining the titanium-doped high-nickel ternary positive electrode material in this embodiment has a charge and discharge voltage of 2.7 to 4.5 V and a current density of 1 C (200 mA / g). The first discharge specific capacity is 211.1 mAh / g, the charge specific capacity is 232.7 mAh / g, and the first charge and discharge coulomb efficiency is 90.71%. After 100 cycles, the discharge specific capacity can still be as high as 197.1 mAh / g, and the capacity retention rate is 93.37%. At a current density of 5 C (1000 mA / g), the first discharge specific capacity is 182.2 mAh / g, the charge specific capacity is 211.6 mAh / g, and the first charge and discharge coulomb efficiency is 86.11%. After 150 cycles, the discharge specific capacity can still be as high as 156.1 mAh / g, and the capacity retention rate is 85.68%. This indicates that the method of preparing titanium-doped high-nickel ternary positive electrode materials is beneficial to the transmission of lithium ions during high-voltage and high-rate charge and discharge cycles, and the discharge specific capacity, charge and discharge performance, and coulombic efficiency are stable, and the cycle performance is good.
[0045] like Figure 5 As shown in the figure, the rate curve of the battery assembled by the method of obtaining the titanium-doped high-nickel ternary positive electrode material in this embodiment, at 2.7-4.5 V and a current density of 10 C (2000 mA / g), the discharge specific capacity can reach 174.4 mAh / g. After 150 cycles, the discharge specific capacity can still be as high as 142.2 mAh / g, and the capacity retention rate is 81.53%, which further illustrates that the high-nickel ternary material is modified with titanium monoxide, and the lithium ion transmission performance is improved during the charge and discharge cycle, and it can still provide excellent electrochemical performance under high voltage.
[0046] Example 2 The positive electrode material is made of titanium-doped high-nickel ternary positive electrode material LiNi 0.9 Co 0.05 Mn 0.05O2, the titanium oxide content in the titanium-doped high-nickel ternary positive electrode material accounts for 0.5% of the positive electrode material, LiNi 0.9 Co 0.05 Mn 0.05 O2 is a spherical secondary particle agglomerate with an average particle size of 3 μm, regular morphology and uniform distribution.
[0047] The method for preparing the titanium-doped high-nickel ternary positive electrode material in this embodiment includes the following steps: (1) Same as step (1) in Example 1; (2) Same as step (2) in Example 1; (3) 0.005 g of titanium monoxide powder obtained in step (2) was mixed with 1.0 g of high-nickel ternary LiNi 0.9 Co 0.05 Mn 0.05 The O2 cathode material is fully mixed and uniformly in the ball mill; (4) The powder obtained in step (3) is transferred into a tube furnace and heated to 400°C at a rate of 5°C / min under an argon atmosphere, sintered for 4 h, and cooled to room temperature to obtain a titanium-doped high-nickel ternary positive electrode material.
[0048] Battery assembly: same as in Example 1; The battery assembled with the titanium-doped high-nickel ternary positive electrode material obtained in this embodiment has a first discharge specific capacity of 179.2 mAh / g, a charge specific capacity of 220.6 mAh / g, and a first charge and discharge coulomb efficiency of 81.22% at a charge and discharge voltage of 2.7 to 4.5 V and a current density of 5 C (1000 mA / g). After 150 cycles, the discharge specific capacity can still reach 135.5 mAh / g, and the capacity retention rate is 75.61%. Compared with the test results of Example 1, it is shown that the method of titanium-doped high-nickel ternary positive electrode material in this embodiment is conducive to the transmission of lithium ions during the charge and discharge process, and the discharge specific capacity, charge and discharge performance and coulomb efficiency are stable, and the cycle performance is good, but the amount of titanium monoxide used is small, the surface structure of the material is not completely modified, and the cycle stability is less improved.
[0049] Example 3 The positive electrode material is made of titanium-doped high-nickel ternary positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 O2, the titanium oxide content in the titanium-doped high-nickel ternary positive electrode material accounts for 1.5% of the positive electrode material, LiNi 0.9 Co 0.05 Mn 0.05 O2 is a spherical secondary particle agglomerate with an average particle size of 3 μm, regular morphology and uniform distribution.
[0050] The method for preparing the titanium-doped high-nickel ternary positive electrode material in this embodiment includes the following steps: (1) Same as step (1) in Example 1; (2) Same as step (2) in Example 1; (3) 0.015g of titanium monoxide powder obtained in step (2) and 1.0g of high-nickel ternary LiNi 0.9 Co 0.05 Mn 0.05 The O2 cathode material is fully mixed and uniformly in the ball mill; (4) The powder obtained in step (3) is transferred into a tube furnace and heated to 400°C at a rate of 5°C / min under an oxygen atmosphere, sintered for 4 h, and cooled to room temperature to obtain a titanium-doped high-nickel ternary positive electrode material.
[0051] Battery assembly: Same as Example 1.
[0052] The battery assembled with the titanium-doped high-nickel ternary positive electrode material obtained in this embodiment has a first discharge specific capacity of 170.2 mAh / g, a charge specific capacity of 214.2 mAh / g, and a first charge and discharge coulomb efficiency of 89.34% at a charge and discharge voltage of 2.7 to 4.5 V and a current density of 5 C (1000 mA / g). After 150 cycles, the discharge specific capacity can still be as high as 124.5 mAh / g, and the capacity retention rate is 73.15%. Compared with the test results of Example 1, it is shown that the method of titanium-doped high-nickel ternary positive electrode material in this embodiment is conducive to the transmission of lithium ions during the charge and discharge process, and the discharge specific capacity, charge and discharge performance and coulomb efficiency are stable, and the cycle performance is good, but excessive use of titanium monoxide will cause excessive electrochemical inert substances, resulting in capacity loss.
[0053] Example 4 The titanium-doped high-nickel ternary positive electrode material of this embodiment is the same as that of Embodiment 1.
[0054] The method for preparing the titanium-doped high-nickel ternary positive electrode material of this embodiment comprises the following steps: (1) Same as step (1) in Example 1; (2) Same as step (2) in Example 1; (3) 0.01 g of titanium monoxide powder obtained in step (2) was mixed with 1.0 g of high-nickel ternary LiNi 0.9 Co 0.05 Mn 0.05 The O2 cathode material is fully mixed and uniformly in the ball mill; (4) The powder obtained in step (3) is transferred into a tube furnace and heated to 500°C at a rate of 5°C / min under an oxygen atmosphere, sintered for 4 h, and cooled to room temperature to obtain a titanium-doped high-nickel ternary positive electrode material.
[0055] Battery assembly: Same as Example 1.
[0056] The battery assembled with the titanium-doped high-nickel ternary positive electrode material obtained in this embodiment has a charge and discharge voltage of 2.7 to 4.5 V and a current density of 5 C (1000 mA / g). The first discharge specific capacity is 171.4.mAh / g, the charge specific capacity is 210.6mAh / g, and the first charge and discharge coulomb efficiency is 82.33%. After 150 cycles, the discharge specific capacity can still reach 126.1mAh / g, and the capacity retention rate is 73.57%. Compared with the test results of Example 1, it is shown that the method of titanium-doped high-nickel ternary positive electrode material in this embodiment is conducive to the transmission of lithium ions during the charge and discharge process, and the discharge specific capacity, charge and discharge performance and coulomb efficiency are stable, and the cycle performance is good. However, the modification temperature is too high, resulting in titanium monoxide reacting too quickly on the surface of the material to cause accumulation, forming an uneven surface structure, resulting in a decrease in high-rate lithium ion transmission efficiency, capacity and cycle stability.
[0057] Example 5 The titanium-doped high-nickel ternary positive electrode material of this embodiment is the same as that of Embodiment 1.
[0058] The method for preparing the titanium-doped high-nickel ternary positive electrode material comprises the following steps: (1) Same as step (1) in Example 1; (2) Same as step (2) in Example 1; (3) 0.01 g of titanium monoxide powder obtained in step (2) was mixed with 1.0 g of high-nickel ternary LiNi 0.9 Co 0.05 Mn 0.05 The O2 cathode material is fully mixed and uniformly in the ball mill; (4) The powder obtained in step (3) is transferred into a tube furnace and heated to 300°C at a rate of 5°C / min under an oxygen atmosphere, sintered for 4 h, and cooled to room temperature to obtain a titanium monoxide-modified high-nickel ternary positive electrode material.
[0059] Battery assembly: Same as Example 1.
[0060] The battery assembled with the titanium-doped high-nickel ternary positive electrode material obtained in this embodiment has a charge and discharge voltage of 2.7 to 4.5 V and a current density of 5 C (1000 mA / g). The first discharge specific capacity is 172.8 mAh / g, the charge specific capacity is 215.6 mAh / g, and the first charge and discharge coulomb efficiency is 80.13%. After 150 cycles, the discharge specific capacity can still reach 133.9 mAh / g, and the capacity retention rate is 77.48%. Compared with the test results of Example 1, it is shown that the method of titanium-doped high-nickel ternary positive electrode material in this embodiment is conducive to the transmission of lithium ions during the charge and discharge process, and the discharge specific capacity, charge and discharge performance and coulomb efficiency are stable, and the cycle performance is good, but the modification temperature is too low, which will cause insufficient reaction and irreversible capacity loss.
[0061] Comparative Example 1 The positive electrode material is made of high nickel ternary positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2 is a spherical secondary particle agglomerate with an average particle size of 3 μm, regular morphology and uniform distribution.
[0062] The preparation method of the high nickel ternary positive electrode material of this comparative example comprises the following steps: (1) Same as step (1) in Example 1; (2) Same as step (2) in Example 1.
[0063] Battery assembly: Same as Example 1.
[0064] The battery assembled with the unmodified high-nickel ternary positive electrode material obtained in this comparative example has a charge and discharge voltage of 2.7 to 4.5 V and a current density of 1C (200 mA / g). The first discharge specific capacity is 210.3 mAh / g, the charge specific capacity is 248.8 mAh / g, and the first charge and discharge coulomb efficiency is 84.52%. After 80 cycles, the discharge specific capacity is 179.5 mAh / g, and the capacity retention rate is 85.36%. At a current density of 5C (1000 mA / g), the discharge specific capacity is 177.2 mAh / g. After 150 cycles, the discharge specific capacity is only 121.5 mAh / g, and the capacity retention rate is 68.57%. At a current density of 10C (2000 mA / g), the discharge specific capacity is 165.8 mAh / g. Compared with the test results of Example 1, the results of this comparative example show that the irreversible capacity loss of the unmodified material charge and discharge reaction is large, and the cycle stability and rate performance are poor.
[0065] Comparative Example 2 A titanium-doped high-nickel ternary positive electrode material and a preparation method thereof.
[0066] The positive electrode material is made of titanium-doped high-nickel ternary positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 O2, the titanium dioxide content in the titanium-doped high-nickel ternary positive electrode material accounts for 1% of the positive electrode material, LiNi 0.9 Co 0.05 Mn 0.05 O2 is a spherical secondary particle agglomerate with an average particle size of 3 μm, regular morphology and uniform distribution.
[0067] The preparation method of the titanium-doped high-nickel ternary positive electrode material of this comparative example comprises the following steps: (1) Same as step (1) in Example 1; (2) Same as step (2) in Example 1; (3) 0.01 g of titanium dioxide powder obtained in step (2) was mixed with 1.0 g of high-nickel ternary LiNi 0.9 Co 0.05 Mn 0.05 The O2 cathode material is fully mixed and uniformly in the ball mill; (4) The powder obtained in step (3) is transferred into a tube furnace and heated to 400°C at a rate of 5°C / min under an argon atmosphere, sintered for 4 h, and cooled to room temperature to obtain a titanium-doped high-nickel ternary positive electrode material.
[0068] Battery assembly: same as in Example 1; The battery assembled with the titanium dioxide modified high nickel ternary positive electrode material obtained in this comparative example has a first discharge capacity of 201.7 mAh / g at a charge and discharge voltage of 2.7-4.5 V and a current density of 1C (200 mA / g). After 100 cycles, the discharge capacity is 183.1 mAh / g, and the capacity retention rate is 90.77%. Under the same test conditions, compared with the titanium monoxide doped modified high nickel material, the discharge capacity is lower and the capacity retention rate is reduced.
[0069] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Therefore, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the scope of protection of the technical solution of the present invention.
Claims
1. A titanium-doped high-nickel ternary positive electrode material, characterized in that: The titanium-doped high-nickel ternary positive electrode material comprises a high-nickel ternary positive electrode material and a titanium doping element; the titanium doping element is derived from a reducing titanium-containing compound, which is mixed and sintered with the high-nickel ternary positive electrode material to form a doping element; the content of the titanium doping element accounts for 0.5-5wt% of the titanium-doped high-nickel ternary positive electrode material, and the reducing titanium-containing compound includes one or more of titanium monoxide, titanium dichloride, and titanium dibromide.
2. The titanium-doped high-nickel ternary positive electrode material according to claim 1, characterized in that: The chemical formula of the high nickel ternary positive electrode material is LiNi x Co y Mn (1-x-y) O2, wherein 0.75<x<0.95, 0.025<y<0.1; the high-nickel ternary positive electrode material is a spherical secondary particle agglomerate with a particle size of 2-4 μm.
3. A method for preparing the titanium-doped high-nickel ternary positive electrode material as claimed in claim 1 or 2, characterized in that: The following steps are involved: (1) Preparation of nickel-cobalt-manganese hydroxide precursor by coprecipitation reaction; (2) uniformly mixing the nickel-cobalt-manganese hydroxide precursor obtained in step (1) with a lithium source, performing two-stage sintering in an oxidizing atmosphere, and cooling to room temperature to obtain a high-nickel ternary positive electrode material; (3) mixing the high-nickel ternary positive electrode material obtained in step (2) with the reducing titanium source; (4) The mixed powder obtained in step (3) is sintered at high temperature in an inert atmosphere, and cooled to obtain a titanium-doped high-nickel ternary positive electrode material.
4. The preparation method according to claim 3, characterized in that: The step (1) of preparing the nickel-cobalt-manganese hydroxide precursor by coprecipitation reaction comprises pumping the nickel-cobalt-manganese mixed solution into a continuously stirred reactor filled with an ammonia solution, heated and filled with a protective atmosphere, and simultaneously pumping in a complexing agent and a precipitant solution, stirring for coprecipitation reaction, aging, filtering, washing and drying to obtain the nickel-cobalt-manganese hydroxide precursor.
5. The preparation method according to claim 4, characterized in that: The nickel source, manganese source and cobalt source in the nickel-cobalt-manganese mixed solution are soluble nickel salt, soluble manganese salt and soluble cobalt salt respectively; the total molar concentration of nickel, cobalt and manganese ions in the nickel-cobalt-manganese mixed solution is 0.1-3.0 mol / L, and the molar ratio of nickel, cobalt and manganese ions is (7.5-9.5): (0.25-2.5): (0.25-2.5); The feeding rate of the nickel-cobalt-manganese mixed solution is 80-120 mL / h.
6. The preparation method according to claim 4, characterized in that: The complexing agent is an ammonia solution, wherein the mass concentration of ammonia in the ammonia solution is 25-28%; the reaction system is adjusted with the ammonia solution to keep the ammonia concentration at 0.1-5.0 mol / L; The precipitant is one or more of sodium hydroxide, potassium hydroxide or lithium hydroxide, and the molar concentration of the precipitant solution is 1.0-7.0 mol / L; the pH value of the reaction system is adjusted to 10-12 by using the precipitant solution; The volume ratio of the ammonia solution, the precipitant solution and the nickel-cobalt-manganese mixed solution is (0.1-10): (1-2): (1-2).
7. The preparation method according to claim 4, characterized in that: During the coprecipitation reaction, the stirring speed is controlled to be 800-1200 r / min, the temperature is 30-60° C., and the time is 30-50 h; The aging temperature is 30-60°C; The washing comprises washing the filter material with deionized water and ethanol respectively and cross-washing the filter material for no less than 6 times; The drying temperature is 80-100° C. and the drying time is 12-24 hours.
8. The preparation method according to claim 3, characterized in that: In step (2), the two-stage sintering is firstly heating the temperature to 350-550°C at a heating rate of 1-10°C / min, sintering for 2-8h, and then heating the temperature to 550-1000°C at a heating rate of 1-10°C / min, and sintering for 8-20h.
9. The preparation method according to any one of claims 3 to 8, characterized in that: In step (3), the mass ratio of the high-nickel ternary positive electrode material to the reducing titanium source is 1:(0.005-0.05); the titanium source is one or more of titanium monoxide, titanium dichloride, and titanium dibromide.
10. The preparation method according to claim 9, characterized in that: In step (4), the high temperature sintering is to heat the temperature to 300-500°C at a heating rate of 1-10°C / min and sinter for 3-5h; the inert atmosphere is an argon atmosphere and / or a nitrogen atmosphere.
Citation Information
Patent Citations
Preparation method of modified ternary positive electrode material
CN106299340A
Preparation method of titanium-doped lithium iron phosphate cathode material
CN107611413A
Ternary positive electrode material, preparation method and application thereof
CN116247210A
Ionic liquid containing divalent cation and monovalent anion and lubricant composition comprising the same
KR102122544B1
Positive Electrode Active Material for Secondary Battery, Preparation Method Thereof, and Positive Electrode for Secondary Battery Including Same
US20220020983A1
Cited By
Doping modified ternary positive electrode material, preparation method thereof and battery
CN120895640A
Full-concentration gradient positive electrode material with rock salt structure as well as preparation method and application of full-concentration gradient positive electrode material
CN121063597A
Modified high-nickel ternary positive electrode material, preparation method, positive plate and lithium ion battery
CN122267069A
Modified high-nickel ternary positive electrode material, preparation method thereof and lithium ion battery
CN122370358A
Doped co-coated NCM ternary positive electrode material and preparation method thereof
CN122831405A